Cyber extension for transfer of technology in India - S. Arulraj and N.Ravikumar (Journal of Plantation Crops 32 December 2004 :445-453, 2004)
The Information Technology is being increasingly utilized in the Transfer of Technology process in India during the recent d years. CPCRl launched its web site in April 2000 and it is encouraging to note that the web site facilities are being increasingly used by the farming community and other clients. A "user analysis" of email services at CPCRL indicated that farmers from Tamil Nadu, Karnataka and Kerala utilized the services to the maximum extent possible followed by students and entrepreneurs. They used the services mainly for obtaining information on the cultivation details. processing technologies and other institute programmes. Coconut crop continued to be the major focus of the clients' queries followed by cocoa and arecanut. Details on the plan for starting a "Net-work Programme on Cyber Extension in Horticultural Crops" are also indicated in the paper